Impact of transformer model parameters variation on FRA signature - Abu-Siada, Ahmed; Hashemnia, Seyednaser; Islam, Syed; Masoum, Mohammad Sherkat (Institut Teknologi Sepuluh Nopember (ITS), 2012)
Power transformers are critical components within the electrical power network. In the event that a failure occurs in service, the impact can be far reaching. Not only causing extended outages, but costly repairs and potentially serious injury or fatality can result. The concept of Frequency Response Analysis (FRA) has been successfully used as a diagnostic technique to detect winding deformation, core and clamping structure for power transformers. However, because FRA has been relying on graphical analysis, it calls for an expert person to analyse the results. So far, there are no standard codes for FRA interpretation. This paper investigates the impact of parameters variation of a high frequency transformer model based on distributed parameters approach on the FRA signature. The physical meaning of the model parameters allows the identification of the problem inside the transformer and helps in establishing a standard code for FRA signature interpretation.